Pengembangan Desa Binaan DigiWisata Terpadu Melalui Peningkatan Manajemen di Gampong Peunaga Pasi, Aceh Barat - Herri Darsan; Afrizal Tjoetra; Masrizal Masrizal; Fiandy Mauliansyah; Apri Rotin Djusfi; Samwil Samwil; Maulidin Fajri (Universitas Teuku Umar, 2025)
The Integrated DigiWisata Program aims to encourage institutional strengthening and digital transformation of Peunaga Pasi Village in West Aceh Regency as a coastal tourism village based on education, culture, and the environment. This village has a unique geographic character with a combination of beaches, swamps, and a strong tsunami history, as well as a number of local attractions such as a mini waterboom, traditional salt tourism, and educational rides. However, this potential has not been managed in an integrated and professional manner. The main problems faced include the weak institutional structure of the Village-Owned Enterprises (BUMG) and Tourism Awareness Groups (Pokdarwis), the absence of a digital management and financial system, low digital promotion capacity, the lack of integration of tourist attractions into one visit package, and the lack of a waste management system in the tourist area. This has led to low tourist visits and a suboptimal contribution to the local creative economy. Through a collaborative and research-based approach, this empowerment program carries out a series of strategic interventions, ranging from the preparation of institutional documents and BUMG Standard Operating Procedures, training in digital financial recording systems, activating tourism village websites and social media, to building educational showrooms and procuring waste shredders. All activities are designed to strengthen the community's capacity to manage local potential sustainably and independently. This program supports the achievement of the SDGs, the Key Performance Indicators (KPI) of Higher Education, and RIRN's focus on social innovation and strengthening community-based economies. The community empowerment program is designed to run for three years, with the first year being the foundational stage for institutional and technological strengthening, followed by business diversification and digital promotion development, and the third year ending with the independence and model replication phase.